Karakteristik Muslim Ideal Dalam Perspektif Hadis Dengan Metode Tematik - Vina Laela Ramadani; Repa Hudan Lisalam; Siti Kholisoh (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Having ideal Muslim characteristics is the ideal for every Muslim. This study aims to discuss the characteristics of the ideal Muslim according to the hadith perspective. This study uses a qualitative method with a thematic approach. The formal object of this research is the characteristics of the ideal Muslim. The material object is the low characteristics of Muslims in the current era of globalization. The results of this study indicate that hadith themes can be formulated within the theoretical framework of ideal Muslim characteristics in the perspective of hadith including, imitating the morals of the Prophet Muhammad, strengthening aqidah (salimul aqidah), shahihul worship, qowiyul jismi, broad-minded, not wasting time, and beneficial for others. This study discusses that the characteristics of the ideal Muslim are needed in the current era. The conclusion of this study is the importance of being an ideal Muslim with character to be able to balance the times. By following the various characteristics of the ideal Muslim that has been formulated according to the hadith thematic framework.